Relationships Among Moral Distress, Level of Practice Independence, and Intent to Leave of Nurse Practitioners in Emergency Departments: Results From a National Survey. (April 2015) - Trautmann, Jennifer; Epstein, Elizabeth; Rovnyak, Virginia; Snyder, Audrey
Abstract : The aims of this research study were to investigate moral distress among emergency department (ED) nurse practitioners (NPs) and examine relationships between moral distress and level of practice independence as well as intent to leave a position. Moral distress has been studied regarding registered nurses and physicians (MDs) but less so in NPs. It is important to explore moral distress in NPs because they tread a unique path between nursing and physician roles. Moral distress may play a significant role in staff nurses' intention to leave practice, and level of practice independence is found to have a relationship with NPs' intention to leave. A convenience sample of ED NPs was obtained from a mailing list of a national nursing specialty organization, the Emergency Nurses Association. Using a correlational design, survey methods assessed moral distress with the Moral Distress Scale–Revised (MDS-R), level of practice independence with the Dempster Practice Behavior Scale, and intent to leave with self-report. Correlational and regression analyses of data were conducted to characterize moral distress among ED NPs and associations between moral distress, level of practice independence, and intent to leave. Results found ED NPs do experience moral distress with poor patient care results from inadequate staff communication and working with incompetent coworkers in their practice. The MDS-R was a significant predictor of intention to leave among respondents. This study is the first of its kind to explore moral distress in ED NPs. Results suggest moral distress influences ED NPs' intent to leave their position. Further studies are needed to explore the findings from this research and to formulate interventions to alleviate moral distress in ED NPs and improve retention in the clinical setting.